2015
DOI: 10.1139/gen-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

SNP in pre-miR-1666 decreases mature miRNA expression and is associated with chicken performance

Abstract: Polymorphisms in miRNA genes could potentially alter various biological processes by influencing the processing and (or) target selection of miRNAs. The rs14120863 (C > G) mutation, which we characterized in a Gushi-Anka F2 resource population, resides in the precursor region of miR-1666. Association analysis with chicken carcass and growth traits showed that the SNP was significantly associated with carcass weight, evisceration weight, breast muscle weight, leg muscle weight, and body weight at 8 weeks of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…Several studies have reported that the SNPs in pre-miRNAs could reduce the production of mature miRNAs [16, 17]. Consistent with these related studies, the expression levels of these three miRNAs were all down-regulated with mutant alleles.…”
Section: Discussionsupporting
confidence: 75%
“…Several studies have reported that the SNPs in pre-miRNAs could reduce the production of mature miRNAs [16, 17]. Consistent with these related studies, the expression levels of these three miRNAs were all down-regulated with mutant alleles.…”
Section: Discussionsupporting
confidence: 75%
“…Mutations that destabilize the region below the terminal loop in Arabidopsis precursor miR172a resulting in an open structure abolishes miR172 expression while mutations that stabilize the structure of the loop do not affect miR172a biogenesis 36 . An SNP in pre- miR1666 decreases mature miRNA expression and is associated with chicken growth traits 37 . Structurally different alleles of Arabidopsis precursor miR824 likely show differential processing of mature miR824 in A. thaliana 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In livestock, SNPs in miRNAs and their target genes are also found to be associated with significant production traits, such as growth, fatness, and meat traits 26 29 , however, the number of such studies is very scarce. It may stem from i.a.…”
Section: Introductionmentioning
confidence: 99%